Kemampuan Literasi Informasi Berdasarkan Model Bruce’s Seven Faces Mahasiswa Jurusan Pendidikan Olahraga Angkatan 2018 Fakultas Ilmu Keolahrgaan Universitas Negeri Padang - Abelza Gevanda Rahwal; Ardoni Ardoni (JURNAL PENDIDIKAN ROKANIA, 2023)
This study aims to describe the ability of information literacy based on the Bruce's Seven Faces model, Students of the Department of Sports Education Class of 2018, Faculty of Sports Science, Padang State University. This research is a qualitative research with descriptive methods. The population of this study was all students of the Department of Sports Education class of 2018, Faculty of Sports Science, Padang State University with a sample of 78 respondents. The sampling technique in this study used a random sampling technique. The instrument of this study used a questionnaire as the main data. Test the analysis requirements using validity and reliability tests. The data analysis technique used is calculation using the mean to calculate the average value, the grand mean calculation is used to calculate the sum of the entire average of each individual variable. The results of this study show first, the experience of information technology in the category is very high. Secondly, the determination of the source of information in the high category. Third, the process of searching for information in the high category. Fourth, control of information in the high category. Fifth, make the information in the high category. Sixth, develop information in the high category. Seventh, use information on high categories. It can be concluded that the Ability of Information Literacy Based on the Bruce's Seven Faces Model, Students of the Department of Sports Education Class of 2018, Faculty of Sports Science, Padang State University is high.